Frontispiece: Molecular Semiconductor Surfactants with Fullerenol Heads and Colored Tails for Carbon Dioxide Photoconversion. Issue 44 (21st October 2019) - Kunkel, Marius; Sutter, Sebastian; Polarz, Sebastian
Abstract : Artificial Photosynthesis In their Communication on page 15620 ff., S. Polarz et al. present surfactants consisting of dye molecules and a polyhydroxylated fullerene, which self‐assemble into bilayer vesicles that mimic key functions of photosystems II and I.